A suppression of differential rotation in Jupiter’s deep interior - Guillot, T.; Miguel, Y.; Militzer, B.; Hubbard, W. B.; Kaspi, Y.; Galanti, E.; Cao, H.; Helled, R.; Wahl, S. M.; Iess, L.; Folkner, W. M.; Stevenson, D. J.; et al. (Nature (London), 2018)
The determination of Jupiter’s even gravitational moments by the Juno spacecraft reveals that more than three thousand kilometres below the cloud tops, differential rotation is suppressed and the gas giant’s interior rotates as a solid body. Probing the depths of Jupiter The Juno mission set out to probe the hidden properties of Jupiter, such as its gravitational field, the depth of its atmospheric jets and its composition beneath the clouds. A collection of papers in this week's issue report some of the mission's key findings. Jupiter's gravitational field varies from pole to pole, but the cause of this asymmetry is unknown. Rotating planets that are squashed at the poles like Jupiter can have a gravity field that is characterized by a solid-body component, plus components that arise from motions in the atmosphere. Luciano Iess and colleagues use Juno's Doppler tracking data to determine Jupiter's gravity harmonics. They find that the north–south asymmetry arises from atmospheric and interior wind flows. To determine the depths of these flows, Yohai Kaspi and colleagues analyse the odd gravitational harmonics and find that the J 3 , J 5 , J 7 and J 9 harmonics are consistent with the jets extending deep into the atmosphere, perhaps as far as 3,000 kilometres. They conclude that the mass of Jupiter's dynamical atmosphere is about one per cent of Jupiter's total mass. The composition of Jupiter beneath its turbulent atmosphere remains a mystery. If different parts of a spinning object rotate at different rates, then the object probably has a fluid composition. Tristan Guillot and colleagues study the even gravitational harmonics and find that, below a depth of about 3,000 kilometres, Jupiter is rotating almost as a solid body. The atmospheric zonal flows extend downwards by more than 2,000 kilometres, but not beyond 3,500 kilometres, as is also the case with the jets. Jupiter’s atmosphere is rotating differentially, with zones and belts rotating at speeds that differ by up to 100 metres per second. Whether this is also true of the gas giant’s interior has been unknown 1 , 2 , limiting our ability to probe the structure and composition of the planet 3 , 4 . The discovery by the Juno spacecraft that Jupiter’s gravity field is north–south asymmetric 5 and the determination of its non-zero odd gravitational harmonics J 3 , J 5 , J 7 and J 9 demonstrates that the observed zonal cloud flow must persist to a depth of about 3,000 kilometres from the cloud tops 6 . Here we report an analysis of Jupiter’s even gravitational harmonics J 4 , J 6 , J 8 and J 10 as observed by Juno 5 and compared to the predictions of interior models. We find that the deep interior of the planet rotates nearly as a rigid body, with differential rotation decreasing by at least an order of magnitude compared to the atmosphere. Moreover, we find that the atmospheric zonal flow extends to more than 2,000 kilometres and to less than 3,500 kilometres, making it fully consistent with the constraints obtained independently from the odd gravitational harmonics. This depth corresponds to the point at which the electric conductivity becomes large and magnetic drag should suppress differential rotation 7 . Given that electric conductivity is dependent on planetary mass, we expect the outer, differentially rotating region to be at least three times deeper in Saturn and to be shallower in massive giant planets and brown dwarfs.